Quercetin can improve anesthesia induced neuroinflammation and cognitive dysfunction by regulating miR-138-5p/ LCN2 - Linjie Lou; Wanning Yu; Ying Cheng; Quan Lin; Yanyan Jiang; Dalong Wang; Lei Che; Meiqing Du; Shuai Wang; Haining Zhen (BMC Anesthesiology)
Abstract Background Anesthesia can lead to functional cognitive impairment, which can seriously affect postoperative recovery. To investigate the effect and mechanism of quercetin (Que) in anesthetized rats, the study provided a new therapeutic idea for the prevention of cognitive dysfunction caused by anesthesia. Methods Cognitively impaired rats were constructed using Isoflurane (ISO) anesthesia and treated with Que. The capacity of the rats to learn and remember was tested using the Morris water maze test. Rat hippocampal tissues were collected and analyzed for inflammatory factor concentration and miR-138-5p expression using ELISA and qRT-PCR, respectively, and the targeting link between miR-138-5p and LCN2 was verified by dual luciferase reporter. Results Que treatment was found to improve ISO-induced cognitive dysfunction and inhibit the level of hippocampal inflammatory factors in rats. miR-138-5p was down-regulated in rats with cognitive dysfunction, while Que treatment increased miR-138-5p expression. The study found that knockdown miR-138-5p can reverse the positive effects of Que therapy, aggravate cognitive dysfunction, and promote the secretion of TNF-α, IL-1β, and IL-6 in the hippocampus. In addition, LCN2, a target gene of miR-138-5p, was significantly up-regulated in the hippocampus after ISO induction. Conclusion Que may inhibit ISO-induced hippocampal neuroinflammation and ameliorate functional cognitive deficits in rats by modulating miR-138-5p/ LCN2.